(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
: This article discusses the concept of gamification in education and its effectiveness, particularly for 9th-grade students. It defines gamification as the use of game-like elements in non-game contexts, such as education, to increase engagement and motivation.